(untitled) (Global Journal of Management and Business Research, 2013)
Pakistan economy is one those economies that has received a huge amount of foreign aid. Foreign aid has been considered to help capital-deficient economies to fulfill the desired levels of finances to generate growth, increase employment and income, and furthermore, it helps to alleviate poverty levels in the recipient economies. Present study focuses on the analysis of impact of foreign aid on income inequality in Pakistan. Since time series data is used for the analysis so the ADF and Phillip-Perron unit root test are applied to find out each of the time series to be stationary at its first difference. Johansen contegration test and vector error correction models are employed to examine the long run and short run impacts of growth, foreign aid, foreign direct investment, and labor force participation rate on income inequality, respectively. The cointegration test results confirm negative impact of economic growth on income inequality whereas foreign aid, foreign direct investment and labor force participation rate are concluded to have inequality increasing impacts. The results are statistically significant.